Design of MEMs-based reconfigurable antenna - Alam, A. H. M. Zahirul; Ibrahimy, Muhammad Ibn; Mohd Sahar, Norsuzlin; Zamani, Norasyikin (2006)
A reconfigurable triple-band antenna o p erating at 17 .36, 2 3 .5 4 an d 29. 87 GHz using MEMS switches is presented. The reconfigurable triple-band di pole is firstly designed ass um ing ideal switches (ON/OFF). T h e effects of the two MEMS switches on the antenna perform a n ce are studi ed. The design is performed using the 3D ele c tr omagnetic si m u l a tor. The proposed antenna can be f a bricated in easy process steps.